Long‐term outcome comparing histological grades of follicular lymphoma patients treated with immunochemotherapy as first‐line therapy: A retrospective analysis from two institutions. (22nd December 2019) - Mercadal, Santiago; Sancho, Juan‐Manuel; Climent, Fina; Tapia, Gustavo; Pomares, Helena; Carro, Itziar; Sorigué, Marc; Pané, Maria; Domingo‐Doménech, Eva; Encuentra, Maite; Aguilera, Carmen; Oliveira, Ana Carla; et al.
Abstract: Objectives: To clarify the impact of histological grades in follicular lymphoma. Methods: We retrospectively analysed 250 patients diagnosed with FL treated with chemoimmunotherapy: 188 patients were grades 1‐2 and 62 grade 3A. Results: In our series, grade 3A FL patients were older, higher proportion of localised disease and lower bone marrow infiltration at diagnosis comparing grades 1‐2 FL patients. Estimated six‐year progression‐free survival and time to progression showed no differences between both groups [grade 3A: 56% (95%CI: 39%‐73%) and 51% (95%CI: 41%‐61%) vs grades 1‐2:55% (95%CI: 46%‐63%) and 57% (95%CI: 49%‐65%), P = .782 and P = .521, respectively]. Estimated six‐year overall survival was lower, 76% (95%CI: 64%‐88%) for the grade 3A group than grades 1‐2 83% (95%CI: 77%‐89%); P = .044. In addition to that, cumulative incidence curves of death not related to lymphoma at 10 years between groups were as follows: [0.26 (95%CI: 0.25‐0.27) and 0.05 (95%CI: 0.04‐0.06) for G3AFL and G1‐2FL, respectively], P = .010. Grade 3A FL showed in PFS curve no relapses after 6 years. These results were absolutely reproduced in 199 patients receiving R‐CHOP regimen as induction. Conclusions: Our results indicate similar long‐term outcomes in terms of progression‐free survival and time to progression in grades 1‐2 and 3A. No relapses were observed in G3AFL group after 6 years.